Development of Montessori-based teaching materials for slow readers (BASIBA) to improve students' reading skills - Tara Septiarani; Abdul Mukhlis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to develop Montessori-based teaching materials called BASIBA (Low Reading Student Teaching Materials) to improve the early reading skills of first-grade students at MSI 14 Medono. The main problem is the high prevalence of slow readers, caused by a lack of literacy stimulation from parents, monotonous conventional learning methods, and teaching materials that do not suit children's cognitive and sensory needs. This study uses a Research and Development (R&D) approach, utilizing the ADDIE model, with a sample of 30 first-grade students. The analysis stage identified needs through observations and interviews with teachers, revealing that 10 students were unable to recognize letters, 12 had difficulty with double consonants, and only 8 were fluent readers. BASIBA was designed based on Montessori principles: multisensory, concrete, and gradual (letters, syllables, words, sentences), and it is equipped with student worksheets and guide barcodes. Validation by media and materials experts gave a feasibility score of 93% and 93.75% (very feasible). The implementation of BASIBA improved students' early reading skills; the pretest score of 63.43 increased to 80.69, yielding an N-Gain of 0.4460 (44.6%). The teacher's response reached 96.25%, and students showed high enthusiasm. The novelty of the research lies in the development of structured Montessori-based teaching materials specifically for slow-reading students through a multisensory approach in a systematic printed format. This research provides a scientific contribution in the form of innovative early reading teaching materials as an inclusive learning solution to improve basic literacy in elementary schools.